2013
DOI: 10.1111/epi.12073
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events related to extraoperative invasive EEG monitoring with subdural grid electrodes: A systematic review and meta‐analysis

Abstract: Summary Purpose Implantation of subdural grids and invasive electroencephalography (EEG) monitoring is important to define the ictal‐onset zone and eloquent cortex in selected patients with medically refractory epilepsy. The objective of this systematic review is to summarize data about adverse events related to this procedure. Methods English‐language studies published up to July 2012, reporting such adverse events were reviewed. Outcome measures included demographic variables; surgical protocol including num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
203
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(211 citation statements)
references
References 24 publications
6
203
1
1
Order By: Relevance
“…Subdural EEG and SEEG are different approaches to iEEG. Both methods have advantages and disadvantages, and the choice between them is the subject of controversy [5,7,8,9]. Subdural electrodes are widely used given their extensive and intensive electrode points [2,10], whereas deep electrodes are useful due to their 3D characteristics and ability to record from deep structures [11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Subdural EEG and SEEG are different approaches to iEEG. Both methods have advantages and disadvantages, and the choice between them is the subject of controversy [5,7,8,9]. Subdural electrodes are widely used given their extensive and intensive electrode points [2,10], whereas deep electrodes are useful due to their 3D characteristics and ability to record from deep structures [11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown prolonged invasive monitoring to be associated with increased incidence of adverse events by 4% per day after 8 days of monitoring. 2 Hence, prolonged invasive monitoring on a raw surgical bed may be a factor that has limited wider adaptation of prolonged monitoring with subdural electrodes. 14 We expect that increasing experience in different institutions with diverse approaches will result in accumulation of outcome and safety data and probably lead to convergence of different surgical approaches to define the optimal strategy.…”
Section: Discussionmentioning
confidence: 99%
“…We recently read with great interest an article by Arya et al 1 In this study, the authors conducted a PubMed search to identify studies that reported adverse events related to subdural electrode (SDE) implantation and invasive electroencephalography (EEG) monitoring. A total of 21 studies with 2,542 patients met the authors search criteria and were included in the systematic review and metaanalysis.…”
Section: To the Editorsmentioning
confidence: 99%
“…As mentioned in our Methods section, only those studies were excluded which reported patients with only depth electrodes. 1 We included the studies that provided data about both subdural and depth electrodes. The study by Tanriverdi et al 2 reports data from a total of 6,415 electrodes including 2,943 depth electrodes (45.9%) and 2,490 cortical electrodes (38.8%).…”
Section: Disclosurementioning
confidence: 99%